Peran Mahasiswa Program Studi Ekonomi Islam Fakultas Ekonomi Dan Bisnis Universitas Jambi Dalam Meningkatkan Literasi Keluarga Dan Masyarakat Sekitar Tentang Perbankan Syariah - Arni Diana; Amri Amir; Rafiqi . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
The positive movement of sharia banking in the last 2 years has not been accompanied by public literacy about sharia banking, which is only 11% with penetration below 7%. Public literacy regarding sharia banking is very minimal, where a group of individuals only